In-situ production of Ti6Al4V single tracks from a blend of CP-Ti and spheroidized Al-V master alloy powders - Ramosena Lekhetho; Dzogbewu Thywill; du Preez Willie (MATEC Web of Conferences)
In-situ alloying in additive manufacturing is a technique that has been employed to produce high-quality (defect free), cost-effective Ti6Al4V parts. In a previous study, in-situ alloying of a powder blend consisting of spherical, commercially pure titanium and irregularly shaped aluminum- vanadium master alloy powders was investigated. Although the produced parts were 99.9 % dense, they exhibited porosity that could be attributed to an improper fit between the spherical and irregularly shaped powders in the powder blend. To improve the quality of the alloy, the master alloy powders were spheroidized and then blended with the titanium powder to a ratio of 90 % Ti and 10 % aluminum-vanadium to form a completely spherical powder blend. Therefore, the purpose of this study was to employ this powder blend as feedstock in the laser powder bed fusion process to produce single tracks from a range of laser powers and scan velocities at a fixed layer thickness. From the conducted analysis, it was found that single tracks with the desired geometrical characteristics were produced at laser powers of 80 and 150 W at corresponding scan velocities of 0.2 and 0.6 m/s using a layer thickness of 60 um. The identification of these machine parameters signposts the possibility to produce high-quality Ti6Al4V parts from this powder blend.